2022
DOI: 10.1136/jnnp-2022-328994
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effect of sex on disease activity and disability accumulation in multiple sclerosis

Abstract: ObjectiveTo quantify sex differences in activity and severity of multiple sclerosis (MS) and how it depends on disease duration and time since clinical onset.MethodsAll Danish citizens with onset of relapsing MS since 1996 who have received disease-modifying therapy have been followed with annual or biannual control visits with mandatory notification of the Danish Multiple Sclerosis Registry. Men and women were compared by the inverse probability of being female. Relapse rates and changes in the Expanded Disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In a latest MS cohort enrolling 10770 patients, female patients exhibited a slower annualised increase in expanded disability status scale scores. These studies supported the protective role of female in the permeability of brain barriers [ 19 ].…”
Section: Discussionsupporting
confidence: 74%
“…In a latest MS cohort enrolling 10770 patients, female patients exhibited a slower annualised increase in expanded disability status scale scores. These studies supported the protective role of female in the permeability of brain barriers [ 19 ].…”
Section: Discussionsupporting
confidence: 74%
“…It may also be of interest for future studies to examine whether prodromal features are related in any way to the timing of a MS diagnosis, or diagnostic delay. However, a recent study from Denmark found that whilst the time from onset to diagnosis had changed over time (decreased) since the 1950s, it did not differ by sex ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…13 However, a registry study found that in persons with disease onset after the age of 50 years, the risk of reaching EDSS 6 at any given age is lower than in patients with onset earlier in life, which is due to a shorter disease duration with shorter time to accumulate disability in the late-onset group, 14 and in our recently published study using the same registry data, we found that the annualised increase in EDSS was twice as high in patients with onset at age 50 or more than in all patients together. 15 This observation is supported by a smaller study conducted on the British Columbia database, 16 underlying the fact that outcomes deriving from a population-based cohort may not be totally generalisable to different age- or course-defined subgroups of patients with MS.…”
Section: Discussionmentioning
confidence: 92%